Siberian exile and the invention of revolutionary Russia, 1825-1917 exiles, émigrés and the international reception of Russian radicalism - Phillips, Ben (BASEES/Routledge series on Russian and East European studies, 2022)
"Over the course of the nineteenth century Siberia developed a fearsome reputation as a place of exile, often imagined as a vast penal colony and seen as a symbol of the iniquities of autocratic and totalitarian Tsarist rule. This book examines how Siberia's reputation came about and discusses the effects of this reputation in turning opinion, especially in Western countries, against the Tsarist regime and in giving rise to considerable sympathy for Russian radicals and revolutionaries. It considers the writings and propaganda of a large number of different émigré groups, explores American and British journalists' investigations and exposé press articles and charts the rise of the idea of Russian political prisoners as revolutionary and reformist heroes. Overall, the book demonstrates how important representations of Siberian exile were in shaping Western responses to the Russian Revolution"--